2022
DOI: 10.1002/poh2.4
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance and acceptance of hepatic venous pressure gradient measurement in cirrhosis (CHESS1904): An international multicenter study

Abstract: Aim To determine the tolerance and acceptance of hepatic venous pressure gradient (HVPG) measurements in patients with liver cirrhosis. Methods This prospective international multicenter study included 271 patients with cirrhosis who were scheduled to undergo HVPG measurement between October 2019 and June 2020. Data related to the tolerance and acceptance of HVPG measurements were collected using descriptive questionnaires. Results HVPG measurements were technically successful in all 271 patients, with 141 (52… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…38 However, HVPG measurement is not routinely performed in clinical practice because of its invasiveness, high cost, and requirement for operator expertise. 41 In our study, all patients with HCC also had cirrhosis and CSPH, and Spx improved their OS. Moreover, the absence of tumor encapsulation, the presence of MVI, and poor tumor differentiation were found to be independently related to poor long-term survival in these patients.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…38 However, HVPG measurement is not routinely performed in clinical practice because of its invasiveness, high cost, and requirement for operator expertise. 41 In our study, all patients with HCC also had cirrhosis and CSPH, and Spx improved their OS. Moreover, the absence of tumor encapsulation, the presence of MVI, and poor tumor differentiation were found to be independently related to poor long-term survival in these patients.…”
Section: Discussionsupporting
confidence: 51%
“…HVPG of >10 mmHg is the gold standard for defining CSPH 38 . However, HVPG measurement is not routinely performed in clinical practice because of its invasiveness, high cost, and requirement for operator expertise 41 . In our study, all patients with HCC also had cirrhosis and CSPH, and Spx improved their OS.…”
Section: Discussionmentioning
confidence: 60%
“…In addition, it is effective in differentiating between cirrhosis and IPH. Based on the backgrounds, Sun et al reported well tolerance and the safety of the technique in the recently performed prospective international multicenter study 5 ; the technical success of HVPG measurement in all 271 patients with single HVPG measurement in 52% of them, and the complication rate of 0.4%. As for the tolerance of hepatic venous catheterization, the postoperative pain was significantly less than the preoperative expected pain ( p < 0.001) or the intraoperative pain ( p < 0.001), and the intraoperative pain was also significantly less than the preoperative expected pain ( p = 0.036).…”
Section: Discussionmentioning
confidence: 99%